Representations of farmers' in social systems and their agro-pastoral choices in semi-arid environments in Morocco, a comparative study of the regions of Doukkala- Abda - Bassir, Assmaa; El- Assaad, Mohammed (Journal of agricultural, environmental and veterinary sciences, 2020)
This research deals with the subject "Representations of farmers' in social systems and their agro- pastoral choices in semi- arid environments in Morocco, a comparative study of the regions of Doukkala- Abda".The research also aims to achieve the following objectives: Firstly, it provides a description and interpretation of the structure of the farmers' society in relation to their agro- pastoral choices (essential plantations and sheep farming).Secondly, the research gives a description and interpretation of the status of the real estate system in relation to agro- pastoral choices of farmers' (essential plantations and sheep farming). Thirdly, the study introduces a description and interpretation of the importance of urban- rural solidarity in relation to agro- pastoral choices of the farmers’ (essential plantations and sheep farming). This research is based on the following null hypothesis: «There are no statistically significant differences (H0) in the agro- pastoral choices of the farmers’ (essential plantations and sheep farming) in the two units Had Hrara (Abda region) and Tnine Lgharbia (Doukkala region), according to the representations of social systems (age groups, types of holdings, solidarity between urban and rural, status of the real estate system) ». We have adopted a quantitative and statistical verification strategy, which includes parametric and non- parametric data based on two methods: one on documents and archives (monographs, statistics ...), and the other on field observation based on the selection of a random sample of 465 farmers' distributed between the following two regions: 227 farmers in the Doukkala region (Tnine Lgharbia) and 238 farmers in Abda (Had Hrara) during 2016 and the questionnaire. Research has stressed the importance of the middle age groups [45- 54 years] and the types of small and medium holdings [4- 19 Ha] to guide the farmers’ agro- pastoral choices in the regions of Doukkala and Abda with the importance of the Melk lands, in addition to the important aid farmers receive in the framework of urban- rural solidarity. The research has also concluded the rejection of the null hypothesis (H0) and confirmation of the alternative hypothesis (H1) "there are statistically significant differences (H1) in the agro- pastoral choices of farmers according to the representations of social systems". Finally, the research adopted the "IMRAD" method based on four scientific qualities: introduction (I), methodology (M), results (R) and discussion (D).
Keywords: social representations; agro; agro- pastoral systems; semi- arid environments; regions of Doukkala- Abda; Abda; Doukkala